Targeting secondary protein complexes in drug discovery: studying the druggability and chemical biology of the HSP70/BAG1 complex. Issue 37 (25th April 2017) - Evans, Lindsay E.; Jones, Keith; Cheeseman, Matthew D.
Abstract : A non-nucleotide FP-probe was designed to study the mechanism of action and druggability of the secondary HSP70/BAG1 complex. Abstract : Proteins typically carry out their biological functions as multi-protein complexes, which can significantly affect the affinity of small-molecule inhibitors. HSP70 is an important target in oncology, so to study its chemical biology and the drug discovery potential of the HSP70/BAG1 complex, we designed a high-affinity non-nucleotide fluorescence polarisation probe.